Pembuktian Sederhana Dalam Proses Kepailitan Terhadap Perusahaan Pengembang Pasca Surat Edaran Mahkamah Agung Nomor 3 Tahun 2023 - Iswandi, Maya (UI Scholars Hub, 2025)
Abstract After the issuance of Sema No. 3/2023, there were various pros and cons to its implementation. This is because the sema has limited and in quotes has protected development companies from bankruptcy proceedings. Sema No. 3/2023 provides immunity to development companies from bankruptcy because they are deemed not to meet the simple proof that must be met in the bankruptcy process. This provision seems to deny the judicial system that should determine the evidence in a case. This certainly causes degradation of legal certainty and consumer protection. Therefore, this research will discuss simple proof in development companies after the issuance of Sema No. 3/2023. This research will be conducted using normative legal research methods with regulatory, case, and conceptual approaches. This research has found after Sema No. 3/2023, the simple proof mechanism is no longer applied to developer companies. In fact, based on the principle of proof, proof can only be carried out in court. However, the existence of Sema No. 3/2023 has shown a practice that is not in accordance with the principle of proof because the Supreme Court has generalized that all developer companies to be bankrupted do not meet simple proof. Moreover, this has violated the legal certainty and consumer protection principle. Keywords: Bankcruptcy, Developer Companies, Simple Proof Principle